Analyzing Presupposition and Their Persuasive Effect in English Cigarette Advertisement Taglines in Indonesia - Ibrahim, Azhar; Saehu, Andang; Wardoyo, Cipto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Cigarette advertisements in Indonesia have their own appeal and have a tagline that is different from other advertisements. This research discusses the existence of presupposition types and persuasive effect within the taglines of English cigarette advertisements in Indonesia. Finding messages or meanings regarding the product are identified in this research, while at the same time adhering to strict country regulations. This research will apply a current theory on presupposition by Yule with identifying six types of presuppositions: existential presupposition, Factive Presupposition, non-factive presupposition, lexical presupposition, structural presupposition and counterfactual presupposition. The research utilize a qualitative approach, focusing on content analysis which emphasizes the importance of understanding the context and meaning of the data. The result of this reseach collected is categorized by 10 utterances of taglines from 7 brands with 13 products. They are Gudang Garam (GG Shiver), ESSE (ESSE Love Yourself), Marlboro (Marlboro Ice Blast), Dunhill (Dunhill Mild), Djarum (Djarum Super MLD Black Series), Djarum Super (MLD Fresh Cola and L.A Menthol), Camel (Camel Yellow 100’s and Camel Blue), Win (Win Filter, Win Bold, Win Click, Win Kretek). The taglines for the advertisements for these brands in Indonesia have the following views on Presupposition Type and Persuasive Effect, they have strategies which shows the uniqueness of each brand and messages or meanings regarding the product are identified.